Virus quantitation by transmission electron microscopy, TCID₅₀, and the role of timing virus harvesting: a case study of three animal viruses - Malenovska, Hana (Journal of virological methods, 2013)
Quantitation of viruses is practised widely in both basic and applied virology. Infectious titration in cell cultures, the most common approach to it, is quite labour-intensive and alternative protocols are therefore sought. One of the alternatives is transmission electron microscope (TEM) quantitation using latex particles at a known concentration as a reference for counting virus particles. If virus TCID₅₀ is determined in parallel, the ratio of infectious to non-infectious virus particles may be established. This study employs such an approach to compute the number of virus particles and TCID₅₀, and establish their correlation for three viruses: Canine adenovirus 1 (CAdV-1), Feline calicivirus (FCV) and Bovine herpesvirus 1 (BoHV-1). Each of the viruses was grown in five replicates until complete cytopathology was recorded (time 0), then frozen. They were thawed, filter-sterilised and left for additional periods of 16, 32 and 48 h at 37°C. At each time point, the infectious ability of the virus was characterised by TCID50 and the number of virions quantified by TEM, in order to evaluate the influence of timing on virus harvest. The virus particle count determined by TEM did not change for any of the viruses throughout the experiment. The relationship between virus particle counts with TCID₅₀ at time 0 showed good linearity response; their ratio was almost constant. The virus particle-to-TCID₅₀ ratio varied between 146 and 426 (mean±SD: 282±103) for CAdV-1, between 36 and 79 (57±18) for FCV and between 110 and 249 (167±53) for BoHV-1. The proportion of non-infectious particles did not change throughout the experiment for either CAdV-1 or BoHV-1. However, a decrease in virus infectious ability disclosed by TCID₅₀ indicated that the fraction of non-infectious particles in FCV increased 300,000 times when time 0 and 48 h were compared. The quantitation of viruses with TEM is a simple and rapid protocol for virus quantitation but account must be taken of the type of virus and harvesting time as virus counts need not necessarily correlate with virus infectious ability.
Keywords: Animals; Microscopy, Electron, Transmission; Calicivirus, Feline; kultivace virů; buněčné linie; virová nálož; mikrobiální viabilita; Time Factors; časové faktory; psí adenoviry; Virus Cultivation; Cell Line; Herpesvirus 1, Bovine; kočičí kalicivirus; bovinní herpesvirus 1; Viral Load; Adenoviruses, Canine; Microbial Viability; transmisní elektronová mikroskopie; zvířata